Drying modelling of amylose fatty acid complex formation for reducing rapidly available glucose of geographical indication rice during high-temperature fluidisation - Junka, Nittaya; Rattanamechaiskul, Chaiwat (My University, 2022)
This study analysed changes in the available glucose of geographical indication rice, Sang Yod variety, from Thailand after drying through the fluidisation technique in the temperature range of 85–115 °C. When the rice with an initial moisture content of 33.3% dry basis was dried at temperature over 85 °C, starch gelatinisation occurred. As the starch underwent gelatinisation, the orderly structure of the starch granules was partially disrupted. Thus, amylose leached out of the granules and simultaneously formed fatty acids in the rice. This created amylose fatty acid complexes (AFCs). This change was detected from the A and V type crystallinity patterns of the starch and complexes using X-ray diffractometry. When drying the rice at 115 °C, the formation of AFCs resulted in rapidly available glucose of dehulled rice decreasing from a medium-high level to a medium-low level; the slowly available glucose value also increased. The drying modelling was developed based on experimental data to explain the observed changes. The developed mathematical model could predict changes in A type crystallinity with the R2 value and average of relative root mean square error of 0.9855 and 6.34%, while those of the V type changes were 0.9879 and 4.64%, respectively. This data can explain the mechanism underlying the available glucose response observed during drying.
Keywords: Amylose; Available glucose; Drying; Fatty acid complexes; Modelling; Rice